BIOTECHNOLOGICAL WASTEWATER TREATMENT USING STRAINS OF MICROORGANISMS - Tynykulov, M.K.; Sadykov, A.M.; Utaubayeva, A.U.; Kornilova, A.А.; Kuznetsova, M.A.; Derbush, S.N.; Kossanov, S.U. (Eurasian Journal of Applied Biotechnology, 2025)
The article presents the results of biotechnological wastewater treatment using strains of fat-destructive microorganisms. The urgency of the work is the shortage of fresh water and pollution of reservoirs with sewage, which are global problems. The purpose of the research is to study and use microbial strains for biotechnological wastewater treatment. The use of biological methods of modern biotechnology is typical for combating environmental pollution. Biological wastewater treatment using microorganisms is a promising direction in solving these problems. This contributes to solving the following application issues: using anaerobic digestion, disposal of solid household waste and the solid phase of wastewater; biological purification of wastewater and natural waters from organic and inorganic compounds; microbial restoration of contaminated soils capable of neutralizing heavy metals in wastewater sediments; composting, biological oxidation of plant waste (leaf litter, straw, etc.); for the purification of polluted air, the study of biologically active sorbent material. The following methods were applied: sampling of water from the stabilization pond of Astana sewage treatment plants, microbiological analysis; determination of COD, BOD5, chromaticity, pH, turbidity, suspended solids, ammonium and phosphates, study of the conditions of cultivation of strains of microorganisms in order to increase lipase yield, conducting pilot tests of biological products on the basis of sewage facilities in Astana. Based on the results of the studies, strains of microorganisms with high lipolytic activity were selected, and a biological product based on these strains was also studied.